PENGARUH METODE THINK-PAIR-SHARE DAN PROBLEM SOLVING SKILL TERHADAP KETERAMPILAN SOSIAL - Baihaqi Siddik Lubis; Suci Perwita Sari (JURNAL TEMATIK, 2020)
This study aims to see the effect of the think-pair-share method and problem-solving skillson the social skills of elementary school teacher education students. This type of research is a quasiexperimental study with 41 students as the experimental class IV-A Pagi and IV-C1 Pagi as the controlclass student. The instrument used was a questionnaire and the data obtained were analyzed usinganacova test (covariance analysis) with the help of SPSS 22 for the window. The results showed that(1) there was a positive and significant effect of the think-pair-share method on students' social skillswith a significance level of 0.013 <0.05; (2) there is a negative value and a significant effect of problemsolving skills on student social skills with a significance level of 0.725> 0.05; (3) there is a positive andsignificant value for the think-pair-share method and problem solving skills on students' social skillswith a significance level of 0.14 <0.05. Thus it can be ignored that there is an effect of the sharingthinking method and problem solving skills on the social skills of elementary school teacher educationstudents